Epsin N-terminal homology domains perform an essential function regulating Cdc42 through binding Cdc42 GTPase-activating proteins - Aguilar, R.C. (2006)
Epsins are endocytic proteins with a structured epsin N-terminal homology (ENTH) domain that binds phosphoinositides and a poorly structured C-terminal region that interacts with ubiquitin and endocytic machinery, including clathrin and endocytic scaffolding proteins. Yeast has two redundant genes encoding epsins, ENT1 and ENT2; deleting both genes is lethal. We demonstrate that the ENTH domain is both necessary and sufficient for viability of ent1Δent2Δ cells. Mutational analysis of the ENTH domain revealed a surface patch that is essential for viability and that binds guanine nucleotide triphosphatase-activating proteins for Cdc42, a critical regulator of cell polarity in all eukaryotes. Furthermore, the epsins contribute to regulation of specific Cdc42 signaling pathways in yeast cells. These data support a model in which the epsins function as spatial and temporal coordinators of endocytosis and cell polarity. © 2006 by The National Academy of Sciences of the USA.